EFFECT OF FREQUENCY AND RESISTANCE BY TEMPERATURE VARIATION ON LEAD ZIRCONATE TITANATE PIEZOELECTRIC CERAMICS DISC - Pasha, R. A.; Raja, G. (The Nucleus, 2011)
Lead Zirconate Titanate (PZT) piezoelectric ceramics disc has been analyzed for its output peak- to-peak voltage between a temperature range at variable frequencies and resistances. The temperature range selected was between 70ÂºC-160ÂºC. The aim was to determine the real time output peak-to-peak voltage across the thin PZT disc for its reliability analysis at the aforesaid stated conditions. Temperature sensitivity with respect to resistance and frequency was observed. The results indicate that the drop in peak-to-peak voltage was higher at high values of frequencies and resistances. The real time monitoring of PZT disc between 70o C-160o C temperature ranges did not show significant variation in voltage at particular resistance. Insensitivity at this particular temperature range makes these PZT disc reliable for the designing of micro-electromechanical systems within said operating conditions.